Sexually Transmitted Infections in Men Aged 50 Years and Older in a Sexual Transmitted Diseases Clinic of Lisbon, Portugal - Ana Sofia Borges; Margarida Rato; Ana Brasileiro; Cândida Fernandes; Ana Rodrigues (Sociedade Portuguesa de Dermatologia e Venereologia, 2018)
Introduction: Sexually transmitted infections (STIs) are a significant public health problem worldwide. They are more frequent in young men; however the prevalence in older individuals is increasing. The aim of this study was to access the prevalence of STIs diagnosis in men aged 50 years and older. We also aimed to compare the demographic and behavioral characteristics of those diagnosed with STIs and those with non-STI conditions. Methods: We conducted a retrospective study including all men aged 50 years and older who have attended a Sexual Transmitted Diseases (STD) clinic of a central hospital in Lisbon, Portugal, between July 2015 and December 2017. Results: Between July 2015 and December of 2017,  1722 men attended the STD clinic, of which 323 (18.8%) were aged 50 years and older. Out of these 323 men, 137 (41.4%) were diagnosed with a STI, more often anogenital warts (32.9%), genital herpes simplex virus infection (19.7%) and early syphilis (19.0%). The mean age of the patients with a STI was 59.9 years and almost all (90.5%) reported an inconsistent use of a condom (90.5%). The number of men that have sex with men (MSM) was significantly higher in patients with a STI (p = 0,003) than those with a non-STI diagnosis. Additionally, 40 (29.2%) of these STI patients had been previously infected with the human immunodeficiency virus (HIV) and 33 (24.1%) had a past history for syphilis, which were significantly higher than in patients in patients with a non-STI diagnosis (p = 0.015 and p = 0.001, respectively). Conclusion: Existing data on STI has mainly focused younger population with few studies performed in older individuals. Our study reports a large number of men aged 50 years and older that allows a better understanding of this age group. High levels of unsafe sex and previous diagnosis of HIV and syphilis emphasizes the importance of sexual health promotion in older individuals.